Geothermal Steam Turbine Design at Inlet Pressure of 6.5 Bar and Power of 63 MW - Nawawi, Achmad
Current Geothermal Power Plant (PLTP) Kamojang Unit 4 has 11 bar turbine inlet pressure with 63 MW of power. Turbine inlet pressure of PLTP Kamojang Unit 4 is different from the three previous units, so the connection between units can not be occured. Power generated by this unit will fall down if the steam supply decrease. Wellhead pressure unit 4 continues to decline each year. It is estimated by 2017, the power generation will decrease if there is no reserve well with similar pressure. Nowadays, looking for wells with high pressure are quite difficult. To maintain the turbine power generation, turbine inlet pressure of PLTP Kamojang Unit 4 is lowered to 6.5 bar. In previous studies, all equipment except the steam turbine can be reused without modification. The steam turbine is a major component of geothermal power plants which convert the potential energy of steam into mechanical energy of the turbine shaft. Because of turbine inlet pressure is lowered, the efficiency of the steam turbine in use today will go down because it does not correspond to the initial design. Electricity power generated by geothermal power plant is maintained the same as before, therefore mass flow rate of steam required will increase. This research aims to design a steam turbine for geothermal power plant Kamojang Unit 4 at the turbine inlet pressure of 6.5 bar and power of 63 MW. The design is based on data of PLTP Kamojang Unit 4 were taken on 7 September 2015 and using Microsoft Excel program which is connected with REFPROP. Steam turbine is designed to have the type axial direction flow, the principle of energy conversion is impulse, six stages, double-flow type, method of regulating using the valve arrangement, and has rotational speed of 3,000 rpm. Steam exits at 0.15 bar. The mass flow rate of steam required by steam turbines is 155,10 kg/s or 558,362.42 kg/hour. The average diameter of the turbine first stage is 1,0207 m and the last stage is 1,5308 m. High of nozzle exit side at the first stage is 0.0796 m and the height of the moving blade out side at the last stage is 0.8887 m. Relative efficiency of steam turbine is 79,04 % and the internal efficiency is 74.97 %.